Analysis of Factors Determining Purchasing Decisions at “Pyur For You” Coffee Shop: Digital Marketing Strategy through Instagram - Zainuddin, Nurul Inayah; Rahayu, Puji; Rahmatika, Nur; Rabbani, Afiyah Bakhitah (ARRUS Journal of Social Sciences and Humanities, 2025)
The study investigates the factors influencing consumer decisions and the impact of digital marketing on Instagram for Cafe Pyur For You's marketing strategy. Using a qualitative descriptive approach with observation and interviews, the study finds that Instagram plays a significant role in attracting initial interest from visitors to Café Pyur for You. Many customers discover the café through content on the Explore feature, which drives visits due to curiosity, peer influence, and the desire to relax. Interaction with the content occurs fairly frequently, though it is still dominated by liking and sharing activities, particularly for promotional event content. Several factors influencing consumer decisions include promotions, testimonials, product quality, popularity, and price. Among all these factors, promotions and popularity have the strongest influence. A combination of creative content, active promotions, and authentic experiences is key to attracting interest and building customer loyalty.